Managing selection of wind power generation technologies - Tamošiūnas, Andrius (Business: Theory and Practice, 2018)
The article presents the principled model for managing the selection of wind power generation technologies enabling business organizations to transform rationally their fossil fuel-based business models towards greater renewable energy reliance. The model is aimed at complex improvement of management of the evaluation, selection processes for public and private organizations keen on switching their business models towards greater use of wind power (including (or) other renewable energy-based technologies). The set of measures proposed has a pivotal focus on the economic utility of the latter with respect to balanced and sustained strategic development of business concerned. Accordingly, the model involves tools for solving the following tasks: setting up an evaluation unit revealing critical factors for rational execution of this task; contributing to situation analysis when determining wind power generation options and assessment criteria. In this respect, besides recommendations on managing data collection, the paper also provides a spectrum of criteria for measuring the attractiveness of wind power generation technologies in terms of economic utility. The latter allow to evaluate, compare possible options in a comprehensive and complex manner; improving assessment and selection task involving and rationally utilizing multi-criteria decision analysis measures including possibilities for combination of MCDA tools if needed. In the context of empirical investigations of the evolution of wind power generation technologies in the EU and globally over the last decade, the paper reveals the benefit of the use of the proposed model specifying all its phases to relevant techniques and actions. Results of its application in practice also confirm the prevailing flexibility when adjusting the model to the specifics of activities of public and private organizations as well as of economic sectors at state, county, and municipal levels.